Implementation simulation model to estimate traffic emission - Mohtaseb, Motaz (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2011)
Traffic sectore presents a major contributor to pollution in Palestine. This causes high emissions emitted from vehicles , such as carbon monoxide (CO) , nitrogen oxides (NOx) , particulate matters (PM) , volatile organic compounds (VOCs) and sulphur dioxide (SO2). This work concentrates in making a simulation model to estimate traffic emission by using MOBILE6. Mobile6 is a computer program that estimates emission factors for gasoline-fueled and diesel motor vehicles , and for certain specialized vehicles such as natural-gas- fueled or electric vehicles that may replace them. This model calculates emission factors for 28 individual vehicles. Depend on various conditions, such as ambient temperatures, travel speed , age distribution, fuel volatility, and mileage accrual rates. This model will estimate emission factors for any calendar year between 2002 and 2050, inclusive . vehicles from the 25 most recent model years are considered to be in operation in each calendar year.
no of pages 87 , 25274, ميكانيك 6/2011 , in the store
Keywords: traffic